2018
DOI: 10.1177/1056789518769341
|View full text |Cite
|
Sign up to set email alerts
|

Using a penalty term to deal with spurious oscillations in second gradient finite elements

Abstract: It is well known that it is necessary to introduce a length scale parameter in a continuum damage mechanics model to correctly simulate strain localization. The second gradient model, a special case of kinematically enriched continua, considers an internal length parameter by taking into account the second order derivatives of the displacements in the virtual power principle. In this paper, we show that the original second gradient finite element of Chambon and co-workers can present spurious oscillations, esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In the second gradient model however it is very difficult to choose the appropriate value for the penalization parameter, which in fact has to be very large [24]. The combined use of Lagrange multiplier fields and penalization terms is a way out, as it improves the convergence performance and the sensitivity to the value of the penalization parameter [21] [24] [28]. In this latter case, Eq.13 becomes:…”
Section: Finite Element Mixed Formulationmentioning
confidence: 99%
See 3 more Smart Citations
“…In the second gradient model however it is very difficult to choose the appropriate value for the penalization parameter, which in fact has to be very large [24]. The combined use of Lagrange multiplier fields and penalization terms is a way out, as it improves the convergence performance and the sensitivity to the value of the penalization parameter [21] [24] [28]. In this latter case, Eq.13 becomes:…”
Section: Finite Element Mixed Formulationmentioning
confidence: 99%
“…One particular type of generalized continua, the second gradient model developed by Chambon et al [14] [15] [16] [17], has demonstrated its ability to regularize strain localization in the framework of plasticity [15] [18] [19] and damage mechanics [2] [20] [21]. Shear banding problems [22] [23] [24] [25] and mode I crack propagation [2] can be reproduced up to a certain point.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[22] who adopted a Cosserat type continuum, well suited for granular materials, to correctly model shear banding. This was soon followed with specific kinematically enriched models [23][24][25] and theoretical developments for classical and multiphase porous media and case studies for soils and concrete [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%